Perkembangan Green Banking Di Indonesia Berdasarkan Systematic Literature Review Periode 2019-2026 - Tri Hanani; Novia Rizki; Wulandari Agustiningsih (Program Studi Akuntansi Universitas Islam Lamongan, 2026)
This study aims to analyze the progress of research on green banking in Indonesia. This research uses a systematic literature review (SLR) method, conducting an in-depth review of previous studies. This study employs a Systematic Literature Review (SLR) of publications on green banking in Indonesia, following the PRISMA method. This study limits the research to the keywords